Sistem pengendalian internal pemberian kredit mantap pensiun (Studi kasus pada PT Bank Mandiri Taspen KC Manado) - Pandelaki, Elsa Roviany; Sondakh, Jullie Jeanette; Pinatik, Sherly (Manajemen Bisnis dan Keuangan Korporat, 2025)
Internal control systems are crucial in ensuring the effectiveness of banking operations, especially in the credit sector where default risk is high. PT Bank Mandiri Taspen, focusing on pension-based lending through the Kredit Mantap Pensiun (KMP) program, offers loans to retirees with automatic pension deductions. Although designed as a low-risk product, recent increases in non-performing loans indicate weaknesses in the implementation of internal control mechanisms. This study analyzes the application and effectiveness of the internal control system in the KMP credit process at PT Bank Mandiri Taspen KC Manado using the COSO framework, which includes control environment, risk assessment, control activities, information and communication, and monitoring. Employing a qualitative case study method, data were collected through interviews, observations, and documentation of credit administration processes. Results show that internal controls are generally well implemented, particularly in the control environment and information communication. However, limitations in supervision and data integration weaken the effectiveness of monitoring and risk assessment. The findings reaffirm the relevance of the COSO framework in managing risks within pension-based lending institutions. The study recommends strengthening staff competency, enhancing monitoring mechanisms, and utilizing digital audit tools to prevent credit irregularities. These insights contribute to improving accountability and credit governance in specialized banking sectors.